Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1139/f03-153
|View full text |Cite
|
Sign up to set email alerts
|

Protecting rockfish through gear design: development of a selective flatfish trawl for the U.S. west coast bottom trawl fishery

Abstract: This study evaluated the potential to reduce the bycatch of rockfish (Sebastes spp.) in a flatfish trawl fishery by developing a selective trawl that separates flatfish from rockfish using differences in their behavior as the trawl net approaches. Using an alternate haul, randomized block design, we compared catches between a commonly used combination trawl and a newly designed, low-rise trawl incorporating a "cutback" headrope. For most of the target flatfish species, the experimental trawl had a 25–59% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…For example, bycatch of Pacific halibut often curtails fishing effort in other Alaskan flatfish fisheries. If it can be adequately demonstrated that the initial behavioral response of halibut at night causes them to rise further off the bottom than do rock sole, then use of low-rise trawls (King et al, 2004;Hannah et al, 2005) may facilitate halibut escape, reducing bycatch and thereby allowing expanded effort on the targeted species. Lastly, these conclusions are based upon the study of sub-adult individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bycatch of Pacific halibut often curtails fishing effort in other Alaskan flatfish fisheries. If it can be adequately demonstrated that the initial behavioral response of halibut at night causes them to rise further off the bottom than do rock sole, then use of low-rise trawls (King et al, 2004;Hannah et al, 2005) may facilitate halibut escape, reducing bycatch and thereby allowing expanded effort on the targeted species. Lastly, these conclusions are based upon the study of sub-adult individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, flatfish may simply rise to a height that allows them to fall back into the net without contacting the footrope (Bublitz, 1996). Again, these maneuvers occur close to the seafloor, typically <1 m (Main and Sangster, 1981;Bublitz, 1996;Rose, 1996;King et al, 2004). This contrasts with the net entry behavior demonstrated by many roundfish (Main and Sangster, 1981;Wardle, 1993;Rose, 1996).…”
Section: Flatfish Behavior Relative To Trawlsmentioning
confidence: 99%
“…Scientists and managers are addressing each of these issues as related to conservation of Pacific rockfish Sebastes spp. Recent examples include modified trawl gear that reduces bycatch of some rockfish yet maintains or increases flatfish catch (King et al 2004), the linking of bocaccio rockfish Sebastes paucispinis recruitment to oceanographic conditions (Tolimieri & Levin 2005), and a theoretical study suggesting that lingcod Ophiodon elongatus predation on juvenile bocaccio can reduce the efficacy of nearshore marine protected areas designed to rebuild bocaccio stocks (Mangel & Levin 2005).…”
Section: Discussionmentioning
confidence: 99%